Unravelling effects of resorcinol: morphological alterations in the retina and thyroid follicles of zebrafish (Danio rerio) embryos - Ben Chabchoubi, Imen; Stoll, Marian; Rinderknecht, Maximilian; Reger, Luisa; Behnstedt, Laura; Braunbeck, Thomas; Baumann, Lisa; Hentati, Olfa; Gölz, Lisa (Aquatic toxicology, 2026)
The hypothalamus-pituitary-thyroid (HPT) axis is a central endocrine regulatory network crucial for morphological development and physiological homeostasis in vertebrates. It is particularly sensitive to disruption by Endocrine Disrupting Chemicals (EDCs), which may lead to adverse effects at the individual and population levels. Resorcinol, an environmentally relevant compound used extensively in industry and cosmetics, has been identified as a potential disruptor of the thyroid hormone system (THS). However, data on its effects in aquatic organisms, especially fish, remain scarce. Recent studies and adverse outcome pathways (AOPs) even suggest a link between thyroid hormone system (THS) disruption and retinal layer alterations in fish. In this study, transgenic Tg(tg:MA-mCherry) zebrafish (Danio rerio) embryos were exposed to resorcinol for 120 h to assess effects on thyroid follicle morphology, retinal development and behaviour. Thyroid follicles were analysed using in vivo fluorescence microscopy. Retinal layers were evaluated histopathologically and behaviour changes were assessed using the light-dark locomotion test. Exposure to 1 and 30 mg/L resorcinol resulted in thyroid follicle proliferation, likely indicating a compensatory response to inhibited thyroid hormone synthesis. At 100 mg/L, reduced eye size and thinning of multiple retinal layers were observed, suggesting secondary developmental effects. Additionally, increased locomotor activity was detected in exposed embryos. These findings support the classification of resorcinol as a THS-disrupting compound and emphasize the need to incorporate histopathological and behaviour endpoints into existing OECD test guidelines to improve the detection of THS disruptors in fish.
Online verfügbar: 10. November 2025, Artikelversion: 15. November 2025
Gesehen am 27.01.2026